Azobenzene photocontrol of peptides and proteins. Issue 83 (19th August 2016) - Mart, Robert J.; Allemann, Rudolf K.
Abstract : Significant advances have been made in the use of light as a stimulus to control biomolecular interactions in biological systems. This article places recent developments in context, illustrating their importance. Abstract : The last few years have witnessed significant advances in the use of light as a stimulus to control biomolecular interactions. Great efforts have been devoted to the development of genetically encoded optobiological and small photochromic switches. Newly discovered small molecules now allow researchers to build molecular systems that are sensitive to a wider range of wavelengths of light than ever before with improved switching fidelities and increased lifetimes of the photoactivated states. Because these molecules are relatively small and adopt predictable conformations they are well suited as tools to interrogate cellular function in a spatially and temporally contolled fashion and for applications in photopharmacology.